Paṇṭāra Vaṉṉiyaṉ viḻā malar - Lōkēsvaraṉ, Kē. Ci (1982)
Volume brought out at the dedication of a statue for Pandara Vanniyan, Chieftain of Vavuniya Kingdom, who fought against the British; comprises papers on the history, literature, and culture of Vavuniya.